2023
DOI: 10.1002/ejhf.3103
|View full text |Cite
|
Sign up to set email alerts
|

Risk of readmission and death after hospitalization for worsening heart failure: Role of post‐discharge follow‐up visits in a real‐world study from the Grand Est Region of France

Guillaume Baudry,
Ouarda Pereira,
Kévin Duarte
et al.

Abstract: AimsPatients who experience hospitalizations due to heart failure (HF) face a significant risk of readmission and mortality. Our objective was to evaluate whether the risk of hospitalization and mortality following discharge from HF hospitalization differed based on adherence to the outpatient follow‐up (FU) protocol comprising an appointment with a general practitioner (GP) within 15 days, a cardiologist within 2 months or both (termed combined FU).Methods and resultsWe studied all adults admitted for a first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…4 By comparison, accompanying data from GWTG-HF in 2021-2022 demonstrated that discharge rates of triple and quadruple guideline-directed medical therapy (GDMT) for HF with reduced ejection fraction (HFrEF) were only 31% and 9%, respectively. 5 In this issue of the Journal, Baudry et al 6 present a real-world observational analysis from the French Health Insurance Database examining the association between early post-discharge follow-up and subsequent rehospitalization and mortality. Patients hospitalized for HF for the first time between 2016 to 2020 in any department were included.…”
mentioning
confidence: 99%
“…4 By comparison, accompanying data from GWTG-HF in 2021-2022 demonstrated that discharge rates of triple and quadruple guideline-directed medical therapy (GDMT) for HF with reduced ejection fraction (HFrEF) were only 31% and 9%, respectively. 5 In this issue of the Journal, Baudry et al 6 present a real-world observational analysis from the French Health Insurance Database examining the association between early post-discharge follow-up and subsequent rehospitalization and mortality. Patients hospitalized for HF for the first time between 2016 to 2020 in any department were included.…”
mentioning
confidence: 99%